Study and characterisation of the post processing ageing of sago pith waste biocomposites - Lai, Jau Choy (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper reports the post-processing ageing phenomena of thermoplastic sago starch (TPS) and plasticised sago pith waste (SPW), which were processed using twin-screw extrusion and compression moulding techniques. Wide angle X-ray diffraction (XRD) analyses showed that after processing, starch molecules rearranged into VH-type (which was formed rapidly right post processing and concluded within 4 days) and B-type (which was formed slowly over a period of months) crystallites. Evidence from Fourier transform infrared spectroscopy (FTIR) analyses corroborated the 2-stage crystallisation process, which observed changes in peak styles and peak intensities (at 1043 and 1026 cm-1) and band-narrowing. Thermogravimetric analysis (TGA) studies showed that the thermal stability of plasticised SPW declined continuously for 90 days before gradual increments ensued. For all formulations tested, post-processing ageing led to drastic changes in the tensile strength (increased) and elongation at break (decreased). Glycerol and fibres restrained the retrogradation of starch molecules in TPS and SPW.